Experimental Study on the Effect of Wet-Dry Cycles on Chloride Ion Penetration in Reinforced Concrete - Noviana, Dwi (Journal of Engineering and Science, 2024)
Corrosion of reinforcement due to chloride ion penetration from seawater significantly affects the durability of reinforced concrete structures. The diffusion of chloride ions into concrete accelerates this degradation. The present study monitors corrosion potential on concrete surfaces using the half-cell potential method and measures chloride ion penetration depth via the chloride colorimetric method. Findings indicate that wet-dry cycles accelerate chloride ion penetration, with longer soaking intervals correlating with increased corrosion levels. Within 30 days, concrete initially free of corrosion exhibited potential values ranging from -417 mV to -489.3 mV after wet-dry treatment. Furthermore, colorimetric analysis revealed clear differences in ion diffusion before and after treatment.